Total Damages Quantification Method for Float Allocation - Jadallah, Khaled M. S. (2016)
A Master of Science thesis in Civil Engineering by Khaled M. S. Jadallah entitled, "Total Damages Quantification Method for Float Allocation," submitted in July 2016. Thesis advisor is Dr. Sameh Monir El-Sayegh. Soft and hard copy available.